CONTENTS OF THE CONCEPT OF HUMAN CAPITAL IN THE CONTEXT OF APPLICATION TO THE INNOVATIVE POTENTIAL OF THE REGION - S. Kalyugina; O. Mukhoryanova; M. Simankina (Вестник Северо-Кавказского федерального университета)
The article considers the concept of innovative development of a region, human capital and its features, depending on the type of socio-economic system. The structure of the region S human capital, which consists of health capital, education capital and culture capital, is determined. Using the example of the Stavropol Territory, these basic components are considered, which allow us to conclude that the region's human potential is quite high. The paper discusses the most popular ways of managing the development of a regional innovation system, confirmed by legal acts or projects. Implemented in the Stavropol Territory. A comparative analysis of the linear and non-linear cycle of innovation is carried out, the interdependence of innovative human capital and innovative development of the region is determined. In general the essence of the article lies in the formation of a systematic approach to the concept of human capital and the main sources of its formation, a description of the main characteristics of human capital and how to manage it.